TI_GERICHTE 11.2016.32 vom 29. November 2017 , Iscrizione definitiva di ipoteca legale degli artigiani e degli imprenditori - TI Tribunale d'appello (2017)
Iscrizione definitiva di ipoteca legale degli artigiani e degli imprenditori